Environmental risk of trace metals and metalloids in estuarine sediments: An example from Southampton Water, U.K. (May 2022) - Celis-Hernandez, Omar; Cundy, Andrew B.; Croudace, Ian W.; Ward, Raymond D.
Abstract: Industrial and commercial port activities are widely recognized worldwide as an important source of pollution to proximal estuaries. In this study, we analysed geochemical and sedimentological parameters including major and trace elements, organic matter and sediment texture in surface sediments from the estuarine environment of Southampton Water, U.K. Using these data, and multivariate statistical tools [correlation, factor and cluster analysis and pollution indices such as Enrichment Factor (EF), Pollution Load Index (PLI) and the Adverse Effect Index (AEI)], we examine sedimentary trace metal and metalloid contamination, contamination sources, and potential biological impacts of the contamination present. The geochemical data, multivariate statistical analysis and pollution indices indicate that the spatial distribution of trace metals and metalloids is influenced by both sediment composition (and mixing) and anthropogenic activities. Most trace metal and metalloid concentrations are close to local geological background levels, except for Cu, Zn and Pb. The spatial distribution of these elements indicates that the Exxon oil refinery, Southampton port, local marinas and runoff from domestic and industrial activities act effectively as point sources of these elements. Pollution indices calculations highlight a degraded environment as a result of these pollutants, and further work is needed to assess the current impact of trace metals and metalloids on local ecology. Graphical abstract: Sub-tidal sediments show enrichment of some trace element concentrations interpreted as the influence of an oil refinery and port activities within Southampton Water. Unlabelled Image Highlights: Trace metals and metalloids were examined in sediments from Southampton Water, U.K. Geochemical data highlight enrichments in Cu, Zn and Pb in subtidal sediments. Metal distribution is controlled by sediment composition and anthropogenic activity. Pollution indices indicate the estuary is moderately impacted by industrial activity. Further work is needed to assess the current impact of trace metals on local ecology.